Writing Acceptable Descriptive Texts: A Case Study through Pre-service English Teachers’ Reflective Journal - Reswari, Cinthia; Sulistyowati, Nina; Herda, Rozanah Katrina (Universitas Pahlawan Tuanku Tambusai, 2024)
This study is a case study held in one of the writing classes of semester two students of the English Language Education Study Program in one of the universities in Yogyakarta, Indonesia. The aim of this study this to know the process of students in writing acceptable descriptive texts in English through their reflective journal. This study is essential to be done because we need more insights on the process of writing acceptable descriptive texts for pre-service English teachers. In obtaining the data, the researcher provided a reflective journal template that must be filled in by the students in the process of writing the descriptive texts. The result of this study can be categorized into four different points which are 1) the outlining process of pre-service English teachers writing their descriptive texts; 2) the drafting process; 3) the review process; and 4) the finalization of writing acceptable descriptive texts. Hopefully, the result of this study can give more insights and improvements to the teaching and learning of how to write descriptive texts especially for pre-service English teachers.